2012
DOI: 10.1590/s0103-84782012005000039
|View full text |Cite
|
Sign up to set email alerts
|

Produção animal e vegetal em pastagem nativa manejada sob diferentes ofertas de forragem por bovinos

Abstract: Neste trabalho avaliou-se a influência de diferentes ofertas de forragem e suas combinações ao longo do ano sobre a dinâmica do crescimento da pastagem e o desempenho animal. O experimento foi conduzido em área de pastagem natural com novilhas de sobreano mantidas em pastejo contínuo com taxa de lotação variável. Os tratamentos foram ofertas de forragem fixas ao longo do ano: 4; 8; 12 e 16kg de matéria seca 100kg de peso vivo-1 por dia e combinações de 8 na primavera e 12 no outono-inverno-verão (8-12%); 12 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
0
13
4
2
Order By: Relevance
“…Our results had SR greater than other experiments in natural grassland of RS with FA of 12% (MEZZALIRA et al, 2012;PINTO et al, 2008). However, in our results, the FAr was based in the FM8 and LBMt (considering the percentage contribution of each stracta), differently to the experiments previously mentioned.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…Our results had SR greater than other experiments in natural grassland of RS with FA of 12% (MEZZALIRA et al, 2012;PINTO et al, 2008). However, in our results, the FAr was based in the FM8 and LBMt (considering the percentage contribution of each stracta), differently to the experiments previously mentioned.…”
Section: Resultscontrasting
confidence: 96%
“…bite mass). MEZZALIRA et al (2012) worked with FA protocols obtained value of 1398kg DM ha -1 and 7.9cm for FMa and HLS, respectively, in the FA of 12% with positive animal performance in the autumn-winter period. However, in this experiment, with FMa and HLS similar to the previous experiment, the animal performance was negative during the autumn-winter period, using the sward height of the lower stracta as one of the criteria to adjust the stocking rate.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The only anthropic intervention in the experimental units was the management of grazing intensity via adjustments of forage allowance, so there was no fertilization, irrigation, fire, or mowing. The severe grazing intensity treatment has evolved into an overgrazed pasture during years previous to our experiment, while the moderate grazing intensity was the best treatment in terms of forage productivity and animal performance in the same interval (Soares et al ; Mezzalira et al ). Grassland managed by severe grazing intensity showed several indications of degradation in both soil properties (decreased soil water infiltration, porosity, aggregation, and organic matter content, while increased soil bulk density) (Bertol et al ; Conte et al ) and plant diversity (decreased Shannon Weaver diversity index) (Carvalho et al ; Pinto ) compared to moderate grazing intensity.…”
Section: Methodsmentioning
confidence: 99%
“…In this article, we studied the effect of two different periods of grazing exclusions in paddocks managed for 27 years under intensive or moderate grazing intensities. Previous studies in this experimental site showed great benefits of moderate grazing intensities on both forage and animal production (Soares et al ; Mezzalira et al ). We hypothesized that moderate grazing intensities can act as a structuring factor of species assemblages, which in turn could facilitate the coexistence of a high number of species.…”
Section: Introductionmentioning
confidence: 99%